Weight gain and inflammation regulate aromatase expression in male adipose tissue, as evidenced by reporter gene activity. (5th September 2015) - Polari, L.; Yatkin, E.; Martínez Chacón, M.G.; Ahotupa, M.; Smeds, A.; Strauss, L.; Zhang, F.; Poutanen, M.; Saarinen, N.; Mäkelä, S.I.
Highlights: Aromatase reporter activity was increased in the subcutaneous and gonadal fat of obese male hARO-Luc mice. Obesity-induced adipose tissue inflammation was associated with enhanced aromatase reporter expression. Glucocorticoids, TNFα, and forskolin induced aromatase reporter activity in adipose tissue and mesenchymal stromal cells. Plant polyphenol mixture attenuated adipose tissue inflammation and aromatase reporter activity in obese male subcutaneous fat. Bioavailable polyphenols, nortrachelogenin and pinosylvin, modified aromatase reporter activity in mesenchymal stromal cells. Abstract: Obesity and white adipose tissue (WAT) inflammation are associated with enhanced aromatization in women, but little is known about the regulation of aromatase ( CYP19A1 ) gene expression in male WAT. We investigated the impact of weight gain and WAT inflammation on the regulation of CYP19A1 in males, by utilizing the hARO-Luc aromatase reporter mouse model containing a >100-kb 5′-region of the human CYP19A1 gene. We show that hARO-Luc reporter activity is enhanced in WAT of mice with increased adiposity and inflammation. Dexamethasone and TNFα, as well as forskolin and phorbol 12-myristate 13-acetate, upregulate hARO-Luc activity, suggesting the involvement of promoters I.4 and I.3/II. Furthermore, we show that diet enriched with antioxidative plant polyphenols attenuates WAT inflammation and hARO-Luc activity in obese males. In conclusion, our data suggest that obesity-associated WAT inflammation leads to increased peripheral CYP19A1 expression in males, and that polyphenol-enriched diet may have the potential to attenuate excessive aromatization in WAT of obese men.